Rhinal and hippocampal contributions to spontaneous inter-item binding and verbal memory recall: Evidence from temporal lobe epilepsy. (March 2020) - Grewe, Philip; Neu, Dominik; Aengenendt, Joerg; Woermann, Friedrich G.; Mertens, Markus; Bien, Christian G.; Kissler, Johanna
Abstract: The medial temporal lobes (MTL) play a prominent role in associative memory processing. Still, it is unclear to what extent specific structures within the MTL sub-serve distinct aspects of associative memory. Here, the role of the MTL in forming spontaneous associations in a "naturalistic" setting is investigated applying a word-list memory test not presenting items in an associative fashion. This allows for the differential investigation of item recall and associative binding. Participants included patients with medial temporal lobe epilepsy (mTLE, n = 79) and healthy controls ( n = 58). Memory performance in a verbal list-learning paradigm was analyzed by (1) inter-trial repetitions ("binding", i.e., number of word-pairs consistently recalled over two consecutive trials), and (2) single item recall. In patients, behavioral results were correlated with rhinal cortex and hippocampal volumetric data. Results showed that binding was specifically diminished for patients with mTLE during learning and delayed recall. Moreover, binding predicted behavioral differences in item recall. Notably, hippocampal volumes were correlated with item recall during delayed recall, whereas rhinal cortex volumes were correlated with binding during learning. Our results provide evidence that diminished verbal memory in patients with mTLE at least partly can be attributed to functional reductions in spontaneous inter-trial stimulus binding. Moreover, they demonstrate a process-dependent functional dissociation between rhinal cortex and hippocampus for verbal encoding and recall: While the rhinal cortex is mainly engaged in detecting novel associations, the hippocampus primarily subserves consolidation and recall of associations between stimuli. Our study thus advances current models of the sub-specialization of MTL structures and offers novel evidence that memory formation in the MTL is mediated by associative item-processing, even when stimuli are not presented in an associative fashion per se. Thus, our results provide valuable qualitative insights into mechanisms of memory formation and memory failures in patients with MTL dysfunctions.